2021
DOI: 10.5194/hess-25-5641-2021
|View full text |Cite
|
Sign up to set email alerts
|

Land use and climate change effects on water yield from East African forested water towers

Abstract: Abstract. East African forested mountain regions are vital in generating and supplying water resources to adjacent arid and semi-arid lowlands. However, these ecosystems are under pressure from both climate and land use changes. This study aimed to analyze the effects of climate and land use changes on water yield using the Budyko framework as a first-order conceptual framework assuming steady-state for pristine/protected forested areas. For nine selected forested water towers in East Africa, the amount and di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Africa boasts millions of low-order (first to third order) streams in the major water catchment areas in Eastern, Central, Southern and Western Africa. These streams often drain Afromontane humid regions that have high agricultural potential (Wamucii et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Africa boasts millions of low-order (first to third order) streams in the major water catchment areas in Eastern, Central, Southern and Western Africa. These streams often drain Afromontane humid regions that have high agricultural potential (Wamucii et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3b further illustrates how these deviations from the predictive Budyko curve affect the estimation of water balances, despite that Budyko-simulated Q generally has a strong correlation (r=0.97) with observed Q, with an RMSE of 43.92 mm/yr. The overestimation of runoff in relatively drier catchments and underestimation of runoff in relatively wetter catchments by the Budyko framework were also reported by Wamucii, et al [4]. To further study the interannual variances of Budyko scatter, we also estimated the best-fit w for each catchment using a least square technique with annual time series of water balances, which is referred to as optimized w [40].…”
Section: Application Of the Extended Budyko Frameworkmentioning
confidence: 64%
“…The Budyko framework is a simple and powerful tool to parameterize precipitation partitioning at the mean annual scale, which estimates the evaporative index (EI) as an empirical curvilinear function of the climatic aridity index (AI) [2]. Based on studies around the world, Budyko-type equations were found to accurately estimate long-term water balance, which prompts a great deal of empirical-, theoretical-, and process-based studies [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The above equation is valid under the assumption that basin storage changes can be neglected over long timescales (>10 years). A similar approach has been used to estimate annual runoff in several regions (e.g., Nkiaka et al, 2022; Wamucii et al, 2021; Zhang et al, 2023).…”
Section: Methodsmentioning
confidence: 99%